1999
DOI: 10.2337/diabetes.48.2.310
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine infusion in rats rapidly impairs insulin stimulation of phosphoinositide 3-kinase but does not alter activation of Akt/protein kinase B in skeletal muscle.

Abstract: Glucosamine, a metabolite of glucose via the hexosamine biosynthetic pathway, potently induces insulin resistance in skeletal muscle by impairing insulin-induced GLUT4 translocation to the plasma membrane. Activation of phosphoinositide (PI) 3-kinase is necessary for insulin-stimulated GLUT4 translocation, and the serine/threonine kinase Akt/protein kinase B (PKB) is a downstream mediator of some actions of PI 3-kinase. To determine whether glucosamine-induced insulin resistance could be due to impaired signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
64
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 0 publications
16
64
1
Order By: Relevance
“…Despite this, there was no significant reduction in glucose uptake until 110 min of glucosamine infusion. Insulinstimulated Akt/PKB activity was unaltered by glucosamine [32]. Although those studies were performed on skeletal muscle, similar alterations in insulin signalling may also be effected in vascular tissue, leading to the impaired total flow and capillary recruitment seen here.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Despite this, there was no significant reduction in glucose uptake until 110 min of glucosamine infusion. Insulinstimulated Akt/PKB activity was unaltered by glucosamine [32]. Although those studies were performed on skeletal muscle, similar alterations in insulin signalling may also be effected in vascular tissue, leading to the impaired total flow and capillary recruitment seen here.…”
Section: Discussionmentioning
confidence: 64%
“…While there is some evidence for the former, there are some discrepancies in the findings. One research group [31] reported that insulinstimulated IRS-1 tyrosine phosphorylation was reduced by glucosamine, whereas another [32] found this was preserved in glucosamine-treated rats. When measured 1 min after a bolus injection of insulin, PI3 kinase (PI3K) activity associated with IRS-1 was decreased by glucosamine infusion, on the other hand, when the activity was measured following 2 h of insulin infusion, no effect of glucosamine was observed [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that hyperglycaemia or an increased flux through the hexosamine pathway reduces insulin signalling at the level of PI3′-kinase or Akt in rat skeletal muscle [25,26]. In addition, NEFA concentrations are usually increased in the diabetic state, and increased NEFA concentrations have been shown to substantially reduce PI3′-kinase activity in human skeletal muscle [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus it has been demonstrated in rat skeletal muscle that hyperglycaemia or an increased flux through the hexosamine pathway can influence insulin signalling on the level of PI3′-kinase or Akt [25,26]. It has also been shown that increased NEFA concentrations decrease PI3′-kinase activity in human skeletal muscle [27].…”
mentioning
confidence: 99%